Life cycle-based optimization of agro-industrial energy supply chains - Tan, Raymond Girard R. (Animo Repository, 2011)
Biofuels have become popular in recent years, as a result of growing concerns about climate change coupled with the need to enhance energy security. However, first generation biofuels have been criticized as competing with food production for increasingly scarce agricultural resources. As a result, enhancing the sustainability of biofuel production requires systematic, life-cycle based optimization of agro-industrial supply chains. Such an approach enables environmental impacts to be minimized by taking advantage of opportunities for integration throughout the supply chain, and by making effective use of byproducts. This paper describes a class of models for the optimal design of such energy systems. © 2011 IEEE.